2015
DOI: 10.1155/2016/4941623
|View full text |Cite
|
Sign up to set email alerts
|

Juglanthraquinone C Induces Intracellular ROS Increase and Apoptosis by Activating the Akt/Foxo Signal Pathway in HCC Cells

Abstract: Juglanthraquinone C (JC), a naturally occurring anthraquinone extracted from Juglans mandshurica, could induce apoptosis of cancer cells. This study aims to investigate the detailed cytotoxicity mechanism of JC in HepG2 and BEL-7402 cells. The Affymetrix HG-U133 Plus 2.0 arrays were first used to analyze the mRNA expression exposed to JC or DMSO in HepG2 cells. Consistent with the previous results, the data indicated that JC could induce apoptosis and hyperactivated Akt. The Western blot analysis further revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The forkhead box O1 (Foxo) signaling pathway participates in the regulation of multiple biological processes, including cellular responses to oxidative stress, cellular apoptosis and cell proliferation (31)(32)(33). It was reported that juglanthraquinone C could induce the apoptosis of HCC cells by activating the Foxo signaling pathway (34). PS341 (Bortezomib) was the first proteasome-inhibitor drug to be approved in clinical treatment for multiple myeloma, functioning by mediating targeted therapy against HCC through the Foxo3 signaling pathway (35).…”
Section: Discussionmentioning
confidence: 99%
“…The forkhead box O1 (Foxo) signaling pathway participates in the regulation of multiple biological processes, including cellular responses to oxidative stress, cellular apoptosis and cell proliferation (31)(32)(33). It was reported that juglanthraquinone C could induce the apoptosis of HCC cells by activating the Foxo signaling pathway (34). PS341 (Bortezomib) was the first proteasome-inhibitor drug to be approved in clinical treatment for multiple myeloma, functioning by mediating targeted therapy against HCC through the Foxo3 signaling pathway (35).…”
Section: Discussionmentioning
confidence: 99%
“…FOXO is an important transcription factor that determines cell fate and is associated with a broad range of cellular physiological functions, such as differentiation, apoptosis, cell proliferation, DNA damage and repair and mediating oxidative stress among a wide range of cancers (83,84). The intracellularly initiation pathway of apoptosis induced by the FOXO protein is associated with oxidative stress, which occurs when ROS is released into the cytoplasm (85). The FOXO1 and FOXO3a transcription factors typically actived during oxidative stress causing apoptotic cell injury (86,87).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the PI3K/Akt signaling pathway is associated with LIHC progression, vascular infiltration and metastasis, as well as poor prognosis and a low survival rate in patients with LIHC ( 20 ). Furthermore, the FoxO signaling pathway, which is closely associated with the PI3K/Akt signaling pathway, serves an important role in the occurrence and development of hepatocellular carcinoma ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%